Letter: ginger as anti‐emetic for acute gastroenteritis in children: interpreting evidence gingerly. Authors' reply. Issue 6 (23rd August 2021) - Nocerino, Rita; Cecere, Gaetano; Micillo, Maria; De Marco, Giulio; Ferri, Pasqualina; Russo, Mariateresa; Bedogni, Giorgio; Berni Canani, Roberto
LINKED CONTENT: This article is linked to Nocerino et al and Philips & Abraham papers. To view these articles, visit https://doi.org/10.1111/apt.16404 and https://doi.org/10.1111/apt.16474